Advice from the presidents : the student's guide to reaching the top in business and politics - Thomas, G. Scott (Greenwood Press, 2008)
The same skills and strategies can propel an aspiring executive to the top of any organization, be it the Podunk High School Student Council, the Acme Xylophone Corporation, or the government of the United States of America. The student council president may be an unpaid volunteer, and the Acme CEO may bark out orders in an office that is rectangular, not oval. But the paths that lead to those positions are remarkably similar to the trail that ends so gloriously at the front door of the White House. Author G. Scott Thomas spent two years examining the lives of nearly two hundred presidential c.